(untitled) (Journal Of Educational and Psychological Researches, 2017)
The study aimed to investigate the relationship between the multiple intelligence and the numerical sense. The chosen population of the study was the 4th secondary stage students. The sample consisted of 400 female and male student. The researcher utilized two test; multiple intelligence test which include three categories of intelligence (logical-mathematical, spatial, and linguistics) consisted of (36) item, and the numerical sense test that consisted of (44) item. The two tests were constructed by the researcher himself. The psychometric properties of the test were also verified. The results showed that there was a correlation between the multiple intelligence and the numerical sense as well as the students’ means scores were lower that the theoretical mean.